2015
DOI: 10.1161/strokeaha.115.010844
|View full text |Cite
|
Sign up to set email alerts
|

Location, Infarct Load, and 3-Month Outcomes of Delayed Cerebral Infarction After Aneurysmal Subarachnoid Hemorrhage

Abstract: We prospectively enrolled patients with SAH presenting to an academic neurosurgical referral center (Prince of Wales Hospital, the Chinese University of Hong Kong) in Hong Kong during a 3-year period. Joint CUHK-NTEC Clinical Research Ethics Committee approved the study. This study conformed to the Declaration of Helsinki and written informed consent was obtained from all the participants or their next of kin.The patient inclusion criteria were (1) spontaneous SAH with angiography-confirmed intracranial aneury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Cerebral infarction is common after cerebral aneurysm rupture, 22,23 and prior studies have correlated the cumulative burden of cerebral infarction to poor clinical outcome and cognitive outcomes. 2,3 In this study, we questioned whether differences in cerebral infarction pattern and burden after treatment of ruptured AcomAs by clipping compared with coiling might account for differences in clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral infarction is common after cerebral aneurysm rupture, 22,23 and prior studies have correlated the cumulative burden of cerebral infarction to poor clinical outcome and cognitive outcomes. 2,3 In this study, we questioned whether differences in cerebral infarction pattern and burden after treatment of ruptured AcomAs by clipping compared with coiling might account for differences in clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical outcomes after aneurysm rupture and treatment are influenced by cumulative cerebral infarction burden. 2,3 Furthermore, patients who recover from aneurysm rupture are often left with disabling cognitive deficits that may result in the patient's dependency on others, which is reflect by higher mRS scores. 4,5 The severity of these cognitive deficits has been correlated to the Hunt and Hess Scale (HHS) grade on admission, older age, aneurysm location, and treatment-related brain injury.…”
mentioning
confidence: 99%
“…Although no such DCI-related infarction has been reported in the literature, recent studies concerning the location of cerebral infarctions secondary to DCI help explain the etiology of our patient's unique case. Of the 126 SAH patients analyzed in a prospective study by Wong et al (2015), the majority of DCI infarctions occurred in the deep penetrating branches of the anterior, middle, and posterior cerebral arteries, which included the pericallosal artery and its associated perforating arteries that directly supply the corpus callosum without collaterals [5,7]. On subsequent univariate analyses, such DCI infarctions of the penetrating arteries were also associated with poorer modified Rankin Scale, Montreal Cognitive Assessment, and Mini-Mental Status Examination results and thus a poorer prognosis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 126 SAH patients analyzed in a prospective study by Wong et al (2015), the majority of DCI infarctions occurred in the deep penetrating branches of the anterior, middle, and posterior cerebral arteries, which included the pericallosal artery and its associated perforating arteries that directly supply the corpus callosum without collaterals [5,7]. On subsequent univariate analyses, such DCI infarctions of the penetrating arteries were also associated with poorer modified Rankin Scale, Montreal Cognitive Assessment, and Mini-Mental Status Examination results and thus a poorer prognosis [5]. The tendency of DCI infarctions to occur in deep penetrating arteries is supported by Rabinstein et al (2004), who, in studying the topographical pattern of DCI infarctions in SAH patients, found that isolated deep infarcts, although not the most common among the study population, occurred in 18% of patients, with 60% of such lesions being symptomatic [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation